Pengaruh Ukuran Perusahaan, Profitabilitas, dan Likuiditas terhadap Corporate Social Responsibility Disclosure - Mega Sekarwigati; Bahtiar Effendi (Universitas Matana, 2019)
This research purposes to check the effects of Company Size and Financial Performance on Corporate Social Responsibility Disclosure. This research uses mining companies which is listed in Bursa Efek Indonesia (BEI) within the period of 2014-2016 as the sample. The total number of companies used as a sample is 14 companies with 3 years of observation. The result of simultant test, company size, profitability, and liquidity has an impact on CSRD. While the result of t test showed a significant negative impact of company size and liquidity on CSRD. While profitability has shown no effect on CSRD.